(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article reveals ways to increase the type and volume of products exported to EU countries within the framework of the "GSP+" (Generalized system of preferences), to increase the export potential of local products, to adapt products to international requirements and norms, and to implement them. The role and importance of the effective use of the "GSP+" system of benefits in export activities has been highlighted by the author.